A longitudinal linkage study of occupation and ischaemic heart disease in the general and Māori populations of New Zealand - Barnes LA; Eng A; Corbin M; Denison HJ; 't Mannetje A; Haslett S; McLean D; Ellison-Loschmann L; Jackson R; Douwes J (PLOS)
OBJECTIVES: Occupation is a poorly characterised risk factor for cardiovascular disease (CVD) with females and indigenous populations under-represented in most research. This study assessed associations between occupation and ischaemic heart disease (IHD) in males and females of the general and Māori (indigenous people of NZ) populations of New Zealand (NZ). METHODS: Two surveys of the NZ adult population (NZ Workforce Survey (NZWS); 2004-2006; n = 3003) and of the Māori population (NZWS Māori; 2009-2010; n = 2107) with detailed occupational histories were linked with routinely collected health data and followed-up until December 2018. Cox regression was used to calculate hazard ratios (HR) for IHD and "ever-worked" in any of the nine major occupational groups or 17 industries. Analyses were controlled for age, deprivation and smoking, and stratified by sex and survey. RESULTS: 'Plant/machine operators and assemblers' and 'elementary occupations' were positively associated with IHD in female Māori (HR 2.2, 95%CI 1.2-4.1 and HR 2.0, 1.1-3.8, respectively) and among NZWS males who had been employed as 'plant/machine operators and assemblers' for 10+ years (HR 1.7, 1.2-2.8). Working in the 'manufacturing' industry was also associated with IHD in NZWS females (HR 1.9, 1.1-3.7), whilst inverse associations were observed for 'technicians and associate professionals' (HR 0.5, 0.3-0.8) in NZWS males. For 'clerks', a positive association was found for NZWS males (HR 1.8, 1.2-2.7), whilst an inverse association was observed for Māori females (HR 0.4, 0.2-0.8). CONCLUSION: Associations with IHD differed significantly across occupational groups and were not consistent across males and females or for Māori and the general population, even within the same occupational groups, suggesting that current knowledge regarding the association between occupation and IHD may not be generalisable across different population groups.
Copyright: © 2022 Barnes et al.
Keywords: Adult; Female; Humans; Longitudinal Studies; Male; Middle Aged; Myocardial Ischemia; Native Hawaiian or Other Pacific Islander; New Zealand; Occupational Diseases; Risk Factors; Sex Factors; Surveys and Questionnaires; White People; Young Adult